2023
DOI: 10.1021/acs.energyfuels.2c03339
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Exfoliated, Ti3C2Tx MXene-Dispersed, LaCoO3 and pC3N4-Based Nanocomposites with In Situ Grown Titania through Etching/Oxidation for Stimulating Solar H2 Production

Abstract: The use of a well-designed Ti 3 C 2 MXene with in situ embedded titania nanoparticles to construct a porous carbon nitride (pCN)/LaCoO 3 Z-scheme and S-scheme heterojunction for stimulating solar hydrogen production has been explored. A novel oxidized/etched approach was employed to produce MXene to maximize charge separation in LaCoO 3 perovskite-dispersed pCN. On increasing the HF etching time from 24 to 48 h, the amount of titania embedded over the MXene was increased, enabling 1.71 times more H 2 evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 92 publications
1
14
1
Order By: Relevance
“…The molecular structures of glycerol and methanol consist of more carbon atoms attached to α-hydrogen atoms; thus, they were more favorable to enhance H 2 production . Previously, we investigated various sacrificial reagents and found hydrogen production in the order TEOA > methanol > glycerol . The discrepancy of the results in the current work was due to using TiO 2 , which has more potential to absorb glycerol compared to g-C 3 N 4 which has more potential to absorb TEOA and methanol than glycerol.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The molecular structures of glycerol and methanol consist of more carbon atoms attached to α-hydrogen atoms; thus, they were more favorable to enhance H 2 production . Previously, we investigated various sacrificial reagents and found hydrogen production in the order TEOA > methanol > glycerol . The discrepancy of the results in the current work was due to using TiO 2 , which has more potential to absorb glycerol compared to g-C 3 N 4 which has more potential to absorb TEOA and methanol than glycerol.…”
Section: Resultssupporting
confidence: 82%
“…44 Previously, we investigated various sacrificial reagents and found hydrogen production in the order TEOA > methanol > glycerol. 45 The discrepancy of the results in the current work was due to using TiO 2 , which has more potential to absorb glycerol compared to g-C 3 N 4 which has more potential to absorb TEOA and methanol than glycerol.…”
Section: Characterizationcontrasting
confidence: 57%
“…In this perspective, Ti 3 C 2 /g-C 3 N 4 was hybridized with LaCoO 3 to construct a Z-scheme heterojunction. The Ti 3 C 2 was heated at 300 °C, which was partially converted to TiO 2 to produce TiO 2 /Ti 3 C 2 . The good interface interaction of LaCoO 3 /g-C 3 N 4 dispersed over TiO 2 /Ti 3 C 2 was achieved as shown in Figure d,e.…”
Section: Applications Of Ti3c2 Mxene Based Carbon Nitride For H2 Evol...mentioning
confidence: 90%
“…Several studies have successfully used Ti 3 C 2 /g-C 3 N 4 hybrid materials for photocatalytic CO 2 reduction and hydrogen production. For example, the Ti 3 C 2 /g-C 3 N 4 hybrid material exhibited significantly higher photocatalytic activity for CO 2 reduction. , In many other studies, the Ti 3 C 2 /g-C 3 N 4 hybrid material showed excellent photocatalytic performance for hydrogen production from water under visible light irradiation. , There is some growing research in this field, and some review articles have published, reported the synthesis and use of Ti 3 C 2 MXene for various applications . Recently, we reported the effect of various environmental and synthesis conditions on the properties of Ti 3 C 2 MXene for energy and environmental applications. Similarly, in another review article, recent advances in Ti 3 C 2 based MOF composites for photocatalytic applications have been reported .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation